2019
DOI: 10.1186/s12981-019-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplant outcomes in HIV-positive patients: a systematic review and meta-analysis

Abstract: BackgroundKidney transplantation is now a viable alternative to dialysis in HIV-positive patients who achieve good immunovirological control with the currently available antiretroviral therapy regimens. This systematic review and meta-analysis investigate the published evidence of outcome and risk of kidney transplantation in HIV-positive patients following the PRISMA guidelines.MethodsSearches of PubMed, the Cochrane Library and EMBASE identified 27 cohort studies and 1670 case series evaluating the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…It is preferable to modify ART to avoid these drug-drug interactions, before kidney transplantation is undertaken [149]. An increase in the risk of acute rejection demonstrated in this group has meant that Tacrolimus-based immunosuppression is used preferentially, with some transplant centres also using additional induction therapy [150]. Despite the increased risk of acute kidney transplant rejection amongst PLWHIV, outcomes are similar to the non-infected population [151].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…It is preferable to modify ART to avoid these drug-drug interactions, before kidney transplantation is undertaken [149]. An increase in the risk of acute rejection demonstrated in this group has meant that Tacrolimus-based immunosuppression is used preferentially, with some transplant centres also using additional induction therapy [150]. Despite the increased risk of acute kidney transplant rejection amongst PLWHIV, outcomes are similar to the non-infected population [151].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…Outcomes of liver and kidney transplant in PLWH have been consistent with those in HIVuninfected people, especially in the absence of HCV co-infection [24]. Although higher rates of acute graft rejection in PLWH undergoing SOT are still a matter of concern (in part consequent to difficulties in adapting immunosuppressors concomitantly with certain ARTs), several studies have reported patient and graft survival rates in long-term follow-up of HIV-positive kidney-transplant recipients similar to those who were HIV negative [25][26][27]. Regarding liver transplantation in HIV/HCV co-infected patients, since DAAs became available, SVRs prior to and post liver transplantation are comparable to those of HCV-mono-infected patients [28,29].…”
Section: Discussionmentioning
confidence: 67%
“… 9 Evidences have shown that the allograft and patient survival rates are comparable between the HIV-monoinfected and the HIV-negative kidney transplant recipients. 10 12 However, some studies demonstrated that the HIV-positive recipients had inferior long-term patient survival compared with the HIV-negative. 5 , 13 The difference in survival among these studies could be explained from the changing era of immunosuppression, the different ART used, and the HCV co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation recipients with HIV infection are at higher risk of acute rejection than HIV-negative recipients (the risks are approximately 30% and 10% in the first year after transplantation, respectively). 5 , 6 , 11 There are many hypotheses regarding the high rejection rate, including HIV containing HLA molecules, the memory phenotype of T lymphocytes in HIV-positive patients, HIV-associated immune dysregulation, and cross-reactivity between the virus and donor antigens. 20 22 However, there is growing interest in the drug interactions between ART, especially PIs and CNIs or mTORi.…”
Section: Discussionmentioning
confidence: 99%